Energy Statistics Yearbook 2017 - United Nations (United Nations, 2020)
In this publication, annual data for 230 countries and areas for the period 2014 to 2017 are presented on production, trade and consumption of energy: solids, liquids, gaseous fuels, electricity and heat, covering both renewable and non-renewable sources of energy. In addition, per capita consumption series are also provided for all energy products. Graphs are included to illustrate historic trends and/or changes in composition of production and/or consumption of major energy products.